2013
DOI: 10.1177/0363546513505421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet-Induced Vitamin D Deficiency on Rotator Cuff Healing in a Rat Model

Abstract: It is estimated that 1 billion people worldwide are vitamin D deficient. In the deficient state, acutely injured rotator cuffs may have a reduced ability for tendon healing. Further studies are needed to determine the exact mechanism by which vitamin D affects tendon healing and whether vitamin D supplementation can improve rotator cuff tendon healing and reduce the incidence of retears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 40 publications
0
70
0
Order By: Relevance
“…First, this was an in vivo study that lacked an in vitro evaluation of the potential impact of ICA. Thus, the mechanism of angiogenesis enhancement by ICA was not studied, which may decrease the robustness of our results; Second, we evaluated the effects of ICA on the early stage of tendon-bone healing during repair of RCT (at two and four weeks), but the longer-term effects of ICA were not evaluated; Third, we used a well-established RC reconstruction model, as described previously [43,67,68,69,70], which differs from that used in humans. The single load-to-failure test construct in this study might not be identical to cases of RCT; Fourth, although we evaluated the effect of ICA on osteogenic markers, including AP, and OCN, the role of ICA therapy on calcium homeostasis and its mechanism, however, is not studied.…”
Section: Discussionmentioning
confidence: 99%
“…First, this was an in vivo study that lacked an in vitro evaluation of the potential impact of ICA. Thus, the mechanism of angiogenesis enhancement by ICA was not studied, which may decrease the robustness of our results; Second, we evaluated the effects of ICA on the early stage of tendon-bone healing during repair of RCT (at two and four weeks), but the longer-term effects of ICA were not evaluated; Third, we used a well-established RC reconstruction model, as described previously [43,67,68,69,70], which differs from that used in humans. The single load-to-failure test construct in this study might not be identical to cases of RCT; Fourth, although we evaluated the effect of ICA on osteogenic markers, including AP, and OCN, the role of ICA therapy on calcium homeostasis and its mechanism, however, is not studied.…”
Section: Discussionmentioning
confidence: 99%
“…11,22,[26][27][28][29] In brief, the athymic rats were anesthetized with 2% isoflurane in high-flow oxygen. They were shaved and positioned supine on a specially designed procedure table.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Chung et al [14] , in a study of 272 patients after arthroscopic rotator cuff repair, found that bone mineral density was an independent predictors of rotator cuff healing. In a rat rotator cuff repair model, Angeline et al [37] demonstrated that vitamin D deficiency negatively affects the biomechanical and histological properties of rotator cuff repairs during the early phase of healing. This effect was found to be independent of bone mineral density [37] .…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%
“…In a rat rotator cuff repair model, Angeline et al [37] demonstrated that vitamin D deficiency negatively affects the biomechanical and histological properties of rotator cuff repairs during the early phase of healing. This effect was found to be independent of bone mineral density [37] . Other system diseases have been associated with rotator cuff tearing as well as rotator cuff healing.…”
Section: Muscle-tendon Unit Retractionmentioning
confidence: 99%